Preliminary biomechanical results of a novel pin configuration for external fixation of vertical shear pelvic fractures. Issue 10 (23rd August 2018) - Stewart, Rebecca; Kieser, David C.; Scholze, Mario; Hammer, Niels; Stone, Brad; Hooper, Gary
Abstract : Background: Vertical shear fractures are unstable and potentially life‐threatening injuries that require urgent reduction and stabilization. The aim of this study was to compare the biomechanical efficacy of three different external fixation pin configurations for vertical shear pelvic fractures in a cadaveric model. We hypothesized that a modified external fixation pin configuration with a crestal (CR) pin in the stable hemipelvis and bilateral supra‐acetabular (SA) pins provides the greatest overall stability to axial loading. Methods: The force to failure within a standard standing axial load (maximum 650 N) was tested on 10 human cadaveric pelvises with vertical shear fractures. Three pin configurations were compared including iliac crest (IC), SA and a modified SA frame with a third CR pin on the stable hemipelvis. Both displacement at the posterior pelvis at 650 N and force to failure of >25 mm displacement was recorded. Results: The mean force to failure was highest with CR (499 N), then IC (350 N) and then SA (265 N) pin configurations, being statistically non‐significant ( P  = 0.165). The minimum force to failure followed a similar trend with 296, 68 and 43 N for CR, IC and SA, respectively. About 1/4 CR, 1/4 IC and 2/9 SA pins sustained 650 N or more without failure. Conclusion: It was shown that this new design may reliably withstand a seated physiological load of 250 N. However, none of the three pin configurations tested can reliably withstand a standing load of 650 N. Further experiments are needed to quantify these findings under physiological loading.